Green and Smart Technology with Sensor Applications International Conferences, GST and SIA 2012, Jeju Island, Korea, November 28-December 2, 2012. Proceedings - Cho, Hyun-seob.; Kim, Tai-hoon.; Mohammed, Sabah; Adeli, Hojjat; Oh, Myoung-kwan.; Lee, Keun-Wang.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
This book comprises the refereed proceedings of the two International Conference on Green and Smart Technology, GST 2012, and on Sensor and Its Applications, SIA 2012, held in Jeju Island, Korea, in November/December 2012. The papers presented were carefully reviewed and selected from numerous submissions and focus on the various aspects of green and smart technology with sensor applications.
Keywords: Computer science; Computer communication systems; Software engineering; Algorithms; Information storage and retrieval; Artificial intelligence; Computer Science; Computer Communication Networks; Information Systems Applications (incl. Internet).; Information Storage and Retrieval; Software Engineering; Artificial Intelligence (incl. Robotics).; Algorithm Analysis and Problem Complexity; Electronic books